1991
DOI: 10.2307/2409922
|View full text |Cite
|
Sign up to set email alerts
|

Limits to Reproductive Success in a Partially Self-Incompatible Herb: Fecundity Depression at Serial Life-Cycle Stages

Abstract: Like many angiosperms, Crinum erubescens is partially self-compatible, producing fewer seeds upon selfing than after outcrossing. In this paper we test the relative magnitude of the prefertilization and postfertilization effects of self-incompatibility, inbreeding depression, or both in a natural population of this hermaphroditic tropical herb. We characterize prefertilization effects by examining pollen tube growth, while postfertilization effects are characterized by examination of embryo abortion and seed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 16 publications
1
25
1
1
Order By: Relevance
“…Moreover, the individual components of inbreeding depression in B. sandvicensis are comparable to those of other angiosperms (usually measured in the glasshouse) whose total inbreeding depression is unknown (Agren and Willson 1991;Assouad et al 1978;Manasse and Pinney 1991;Kohn 1988;Jain 1978). However, some gynodioecious angiosperms show little or no inbreeding depression (Ashman 1992;Eckhart 1992) or selffertilization in hermaphrodites (Eckhart 1992;Krohn 1980), and females appear to be maintained through either a maternal effect on seed' quality or direct developmental/physiological advantage to adults that increases fecundity.…”
Section: Relative Ovule Success Female Frequency and Biparental Inbmentioning
confidence: 67%
“…Moreover, the individual components of inbreeding depression in B. sandvicensis are comparable to those of other angiosperms (usually measured in the glasshouse) whose total inbreeding depression is unknown (Agren and Willson 1991;Assouad et al 1978;Manasse and Pinney 1991;Kohn 1988;Jain 1978). However, some gynodioecious angiosperms show little or no inbreeding depression (Ashman 1992;Eckhart 1992) or selffertilization in hermaphrodites (Eckhart 1992;Krohn 1980), and females appear to be maintained through either a maternal effect on seed' quality or direct developmental/physiological advantage to adults that increases fecundity.…”
Section: Relative Ovule Success Female Frequency and Biparental Inbmentioning
confidence: 67%
“…Tomita (1931) demonstrated that these embryos, when produced by Crinum latifolium, were viable. Other experiments have shown that these "naked" embryos occurred only during selfing in Crinum erubescens, and were present in nearly 17% of all selfed fruit (Manasse and Pinney, 1991).…”
Section: Natural Historymentioning
confidence: 91%
“…It is also often of interest to know whether inbreeding depression changes through the life cycle (Charlesworth and Charlesworth 1987;Kalisz 1989;Manasse and Pinney 1991). Generally, fitnesses are measured on offspring from the same parents or on the same individuals over a number oflife stages.…”
Section: Detecting Differences Among Life Stagesmentioning
confidence: 99%